2014
DOI: 10.1016/j.clinbiomech.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pediatric obesity on dynamic joint malalignment during gait

Abstract: Non-obese children showed greater range of motion in the sagittal plane, particularly at the hip and knee. Frontal and transverse plane differences suggest that obese children function in a more genu valgum position than non-obese children. Static measures of genu valgum have been previously associated with pediatric obesity; the findings indicate that there are also dynamic implications of said malalignment in obese children. Genu valgum presents increased risk of osteoarthritis for obese children and should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 26 publications
(30 reference statements)
1
20
0
4
Order By: Relevance
“…These results might be linked to the greater step width and hip internal rotation position above mentioned, which together could be indicating a lower limb valgus position commonly adopted by OW/OB during gait . Some authors have suggested that this valgus position helps provide a better dynamic stability in the frontal plane during gait and that it could be a subconscious strategy to reduce loading on the medial compartment of the knee joint . In agreement with the aforementioned findings in pelvis and hip, OW/OB still presented greater knee abduction power absorption than NW after taking into account their body mass, suggesting again that gait biomechanical alterations of this population are not only explained by the presence of excessive body mass .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These results might be linked to the greater step width and hip internal rotation position above mentioned, which together could be indicating a lower limb valgus position commonly adopted by OW/OB during gait . Some authors have suggested that this valgus position helps provide a better dynamic stability in the frontal plane during gait and that it could be a subconscious strategy to reduce loading on the medial compartment of the knee joint . In agreement with the aforementioned findings in pelvis and hip, OW/OB still presented greater knee abduction power absorption than NW after taking into account their body mass, suggesting again that gait biomechanical alterations of this population are not only explained by the presence of excessive body mass .…”
Section: Discussionsupporting
confidence: 71%
“…We found strong evidence that OW/OB have greater pelvis transversal plane motion and higher hip internal rotation across the entire gait cycle compared with their NW peers . However, we did not find unanimity in kinematic results in the sagittal and frontal planes, and therefore the level of evidence was set as inconsistent.…”
Section: Resultsmentioning
confidence: 63%
“…For the walking trials, kinematic data were digitised and trimmed using Cortex. Kinetic data were filtered using a low pass fourth order Butterworth filter with a cut-off frequency of 6 Hz was used to remove noise (Shultz, D'Hondt, Fink, Lenoir, & Hills, 2014). All dependent variables relating to the walking trials were processed with Visual 3D software (C-Motion, Inc., Germantown, MD, USA) version 5.…”
Section: Discussionmentioning
confidence: 99%
“…For obese patients, however, weight training can add excessive load on joints or bones, together with the increased body mass, and lead to joint injuries 19, 35 . Therefore, non-weightbearing exercises such as swimming, water walking, and cycling that are easy on joints can be suggested as an effective exercise program for obese patients with reduced bone mineral density 30 . Non-weight-bearing exercises are commonly considered inappropriate for improving bone mineral density, since they do not sufficiently stimulate the bones.…”
Section: Discussionmentioning
confidence: 99%